Ответ:
Объяснение:
1
1)a 2)b 3)¬b 4)a∨¬b 5)a∨¬b→b 6)¬a 7) ¬a∨b 8)(a∨¬b→b)∧(¬a∨b)
0 0 1 1 0 1 1 0
0 1 0 0 1 1 1 1
1 0 1 1 0 0 0 0
1 1 0 1 1 0 1 1
2
1)a 2)b 3)a∧b 4)¬a∧b 5)¬a 6)¬a∨b 7)¬a∧b≡(¬a∨b)
0 0 0 1 1 1 1
0 1 0 1 1 1 1
1 0 0 1 0 0 0
1 1 1 0 0 1 0
3
1) а 2)b 3) a→b 4)¬b 5)¬a 6) ¬b→¬a 7) (a→b)⇔(¬b→¬a) 8) F
0 0 1 1 1 1 1 0
0 1 1 0 1 1 1 0
1 0 0 1 0 0 1 0
1 1 1 0 0 1 1 0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
1
1)a 2)b 3)¬b 4)a∨¬b 5)a∨¬b→b 6)¬a 7) ¬a∨b 8)(a∨¬b→b)∧(¬a∨b)
0 0 1 1 0 1 1 0
0 1 0 0 1 1 1 1
1 0 1 1 0 0 0 0
1 1 0 1 1 0 1 1
2
1)a 2)b 3)a∧b 4)¬a∧b 5)¬a 6)¬a∨b 7)¬a∧b≡(¬a∨b)
0 0 0 1 1 1 1
0 1 0 1 1 1 1
1 0 0 1 0 0 0
1 1 1 0 0 1 0
3
1) а 2)b 3) a→b 4)¬b 5)¬a 6) ¬b→¬a 7) (a→b)⇔(¬b→¬a) 8) F
0 0 1 1 1 1 1 0
0 1 1 0 1 1 1 0
1 0 0 1 0 0 1 0
1 1 1 0 0 1 1 0